Penerapan Sistem Pengendalian Intern Pemerintah (SPIP) Pada Kabupaten Gorontalo - Paneo, Fitrianty; Sondakh, Jullie J; Morasa, Jenny (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2017)
Abstract. This study aims to analyze the suitability of GICS implementation in Gorontalo District with Government Regulation Number 60 Year 2008 on  GICS, the obstacles in the implemention of GICS  as well as what efforts have been made to overcome the obstacles of GICS implementation and to increase GICS maturity level in Gorontalo District. This is a qualitative research with case study approach. This study used primary and secondary data. Primary data were obtained from in depth interviews, observation and documentation. On the other hand, secondary data were in the form of documents related to the reseach. The results show that GICSin Gorontalo District has been implemented in accordance to Government Regulation Number 60 Year 2008. However, GICS level 3 (three) maturity targets have not yet been achieved and it means that the implementation of GICS still encounters many obstacles. The obstacles in the application of GICS in Gorontalo District are: 1) insufficient human resource competence, 2) the number of human resources is not in accordance with the needs of organization, 3) limited budget, 4) lack of compliance, 5) evaluation and documentation activities are not maximized yet, and 6) many activities have not been supported by Standard Operational Procedures (SOP). Furthermore, the efforts made to overcome the obstacles of GICS implementation are by 1) encouraging human resources development program such as substantive training and training of their own office, 2) maximizing budget, 3) establishing effective communications, 4) increasing the number of auditors and 5) building organizational commitment.Keywords: Implementation of Government Internal Control System (GICS), GICS Maturity Result, Constraints and efforts Abstrak. Penelitian ini bertujuan untuk menganalisis kesesuaian penerapan SPIP pada Kabupaten Gorontalo dengan PP 60 Tahun 2008 tentang SPIP, mengidentifikasi dan menganalisis kendala dalam penerapan SPIP serta upaya-upaya apa yang dilakukan dalam mengatasi kendala penerapan SPIP untuk peningkatan tingkat maturitas SPIP di Kabupaten Gorontalo. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data yang digunakan adalah data primer, yang diperoleh melalui wawancara mendalam, observasi dan studi dokumentasi. Serta data sekunder berupa dokumen-dokumen terkait dengan penelitian. Hasil penelitian menunjukkan bahwa secara umum penerapan SPIP pada Kabupaten Gorontalo telah sesuai dengan PP 60 Tahun 2008 tentang SPIP. Namun, belum tercapainya target level 3 (tiga) maturitas SPIP di Kabupaten Gorontalo mengindikasikan bahwa penerapan SPIP masih mengalami banyak kendala. Kendala-kendala dalam penerapan SPIP yaitu; 1) kompetensi SDM belum memadai, 2) kuantitas SDM belum sesuai dengan kebutuhan organisasi, 3) terbatasnya anggaran, 4) kurangnya kepatuhan, 5) belum maksimalnya kegiatan evaluasi dan dokumentasi, dan 6) terdapat kegiatan yang belum didukung dengan Standar Operasional Prosedur (SOP). Upaya-upaya yang dilakukan untuk mengatasi kendala-kendala dalam penerapan SPIP yaitu: 1) program pengembangan SDM melalui diklat substantif dan pelatihan kantor sendiri, 2) memaksimalkan anggaran, 3) membangun komunikasi yang efektif, 4) menambah jumlah auditor dan 5) membangun komitmen organisasi.Kata kunci: Penerapan Sistem Pengendalian Intern Pemerintah (SPIP), Tingkat Maturitas Penyelenggaraan SPIP, Kendala dan Upaya.